1990
DOI: 10.1063/1.103253
|View full text |Cite
|
Sign up to set email alerts
|

Insitu preparation of the Gd-Ba-Cu-O superconducting thin films on (100) LaAlO3 by sputtering

Abstract: High-temperature superconductor GdBa2Cu3O7 thin films were grown in situ on LaAlO3 single-crystal substrates by dc magnetron sputtering using a single planar target. 93% samples had a zero resistance transition temperature Tc0 more than 90 K and a transition width less than 1 K. The best films had a Tc0 of 92.5 K, a transition width of 0.57 K, and a critical current density of 3.6×106 A/cm2 at 77 K. The reproducibility is very good. X-ray diffraction analysis showed c axis normal to the film’s surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…different partial pressures of oxygen. As this figure shows, the value of T c of the present TFA-derived GdBCO films is higher than that of YBCO for a wide range of processing parameters, and is comparable to those reported for single crystals [7,14], melt-processed bulk samples [5] and films prepared with dc magnetron sputtering techniques [9,10]. Furthermore, it is very interesting that T c is only weakly affected by the processing conditions and the difference is less than about 1 K for the range of parameters investigated in the present work.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…different partial pressures of oxygen. As this figure shows, the value of T c of the present TFA-derived GdBCO films is higher than that of YBCO for a wide range of processing parameters, and is comparable to those reported for single crystals [7,14], melt-processed bulk samples [5] and films prepared with dc magnetron sputtering techniques [9,10]. Furthermore, it is very interesting that T c is only weakly affected by the processing conditions and the difference is less than about 1 K for the range of parameters investigated in the present work.…”
Section: Resultssupporting
confidence: 81%
“…In the present work, we have turned our attention to gadolinium, one of the light rare-earth elements. Studies using single crystals have shown that GdBa 2 Cu 3 O 7−y [7] has a higher irreversible field than YBa 2 Cu 3 O 7−y [8], and Gd-Ba-Cu-O (GdBCO) films prepared by sputtering methods are reported to exhibit higher T c than YBCO films [9][10][11]. The preparation of GdBCO films with an MOD method that does not use fluorine has been reported previously [12,13].…”
Section: Introductionmentioning
confidence: 99%